2022
DOI: 10.1186/s12866-022-02500-6
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil microbial community structure and function to different altitudes in arid valley in Panzhihua, China

Abstract: Background Altitude affects biodiversity and physic-chemical properties of soil, providing natural sites for studying species distribution and the response of biota to environmental changes. We sampled soil at three altitudes in an arid valley, determined the physic-chemical characteristics and microbial community composition in the soils, identified differentially abundant taxa and the relationships between community composition and environmental factors. Results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Frontiers in Microbiology 09 frontiersin.org and U4 from middle altitudes. Our results agree with those recently reported (Zhang et al, 2022), which found that the microbial community composition of the soil at the middle altitude showed the lowest microbial diversity. It was proposed that this may be caused by altitude or lack of nutrients in the habitat (Wang et al, 2016).…”
Section: A B C Dsupporting
confidence: 93%
See 1 more Smart Citation
“…Frontiers in Microbiology 09 frontiersin.org and U4 from middle altitudes. Our results agree with those recently reported (Zhang et al, 2022), which found that the microbial community composition of the soil at the middle altitude showed the lowest microbial diversity. It was proposed that this may be caused by altitude or lack of nutrients in the habitat (Wang et al, 2016).…”
Section: A B C Dsupporting
confidence: 93%
“…In our study, all the samples were from the same lichen, so the influence of lichen species can be excluded. Therefore, it is likely that U2 geographical environment causes its unique endophytic microbial community structure, such as pH, temperature, and nutrient elements (Zhang et al, 2022). Moreover, the fungal microbial community structure of U3 was also unique, although this feature was not found in the bacterial community (Figure 5).…”
Section: A B C Dmentioning
confidence: 99%
“…Our results suggest that the diversity of bacterial and fungal communities may be more affected by changes in the soil environment. Previous research has demonstrated that soil nutrients are a critical factor influencing microbial communities ( Bayranvand et al, 2021 ; Cheng et al, 2022 ; Xie et al, 2023 ), and that soil nutrients can be influenced by altitude, climate, and vegetation ( Hirao et al, 2021 ; Zhang et al, 2022 ).”…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the relatedness to a different genus cannot alone explain the observed trends, suggesting that even within a genus two strains could respond differently to environmental changes (e.g., strains B and C). Altitude was shown to affect physicochemical characteristics and microbial diversity in soils ( Zhang et al, 2022 ). Therefore, as the strains investigated in the present study were isolated from three soils collected at different altitudes in the French Alps, it cannot be excluded that the specific variations in 3-OH FA relative abundances may at least partly reflect an intrinsic adaptation of each bacterial strain to the habitat it was isolated from.…”
Section: Discussionmentioning
confidence: 99%